The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3844/ajassp.2010.201.207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine on Auditory Brainstem Response Threshold Shift in Rabbits Exposed to Noise and Carbon Monoxide

Abstract: Problem statement: Noise Induced Hearing Loss (NIHL) is one of the most important occupational disease in worldwide. NIHL has been found to be potentiated by simultaneous Carbon monoxide (CO) exposure. Exposure to noise plus CO is common in occupational and environmental settings. Free radicals have been implicated in cochlear damage resulting from exposure to noise and due to CO hypoxia This study examined whether N-Acetylcysteine (NAC) administration cause attenuation of Auditory Brainstem Response (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…Although noise could cause more temporary hearing changes at higher frequencies, NAC and CoQ 10 was more effective on temporary hearing changes at lower frequencies. These findings are consistent with previous research results indicating more effects of antioxidant agents at the frequencies away from the frequencies with greater hearing changes (5). The greatest improvement occurred with NAC rather than CoQ 10 as demonstrated by functional data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although noise could cause more temporary hearing changes at higher frequencies, NAC and CoQ 10 was more effective on temporary hearing changes at lower frequencies. These findings are consistent with previous research results indicating more effects of antioxidant agents at the frequencies away from the frequencies with greater hearing changes (5). The greatest improvement occurred with NAC rather than CoQ 10 as demonstrated by functional data.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of NAC on acoustic trauma has not been consistent in the literature. Administration of NAC before or within 24 hours of noise exposure has provided partial protection from NIHL in most animal studies (4)(5)(6)(7)(8). In contrast, some studies revealed no protective effect of NAC on NIHL (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…As executive functions are mainly managed by the frontal lobe of the brain, these findings support the hypothesis that states "smokers may have defects in their cognitive-executive functions" (Elwood et al, 1999). In this regard, the studies conducted on executive functions and cognitive performances of substance abusers, especially cigarette smokers, showed that nicotine-containing products such as cigarettes can disrupt executive tasks at workplace, where absolute concentration is required (Kalmijn, Van Boxtel, Verschuren, Jolles, & Launer, 2002;Mortazavi et al, 2010).…”
Section: Introductionsupporting
confidence: 67%
“…Brain function and mental performance are affected by psychomotor speed and mental flexibility following damage or injury in the cerebral cortex capillaries; therefore, cigarette smoking can cause some changes in the vascular mechanism for blood flow and some physiological changes in the organs like brain (Mortazavi et al, 2010;Newhouse, Potter, & Singh, 2004). Thus, the smoking mechanism in patients with stroke and dementia has been well-defined through the effect of smoking on the vascular system (Cees De Groot et al, 2000;Raininko & Tilvis, 1993;Rogers, Meyer, Judd, & Mortel, 1985;Terborg, Bramer, Weiller, & Röther, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established the significant role of antioxidants (e.g., N-acetylcysteine and α-Tocopherol) in the prevention and treatment of NIHL caused by the combined exposure to noise and CO (12)(13)(14). Hydrogen gas (H 2 ) has shown to have healing effects in the treatment of several disorders (15).…”
Section: Introductionmentioning
confidence: 99%